Factors Affecting Mothers in Feeding Complementary Feeding for Babies Aged 0-6 Months at Saribudolok Public Health Center - Yunardi; Ratih Angeli Pasaribu; Dewi Wandha Syahputri Daulay (PT Inovasi Pratama Internasional, 2022)
Coverage of exclusive breast milk (ASI) in the working area of the Saribudolok health center is still low, as a result of early complementary feeding (MP ASI) under the age of 6 months. Giving solid foods in this period before the baby's digestive system is ready to accept them, then these foods cannot be digested properly and can cause indigestion, gas, and constipation. Early complementary breastfeeding is closely related to the decisions made by a mother. Data on Indonesia's health profile in 2004 shows that exclusive breastfeeding in Indonesia is still low, namely 41.7%. This research is an analytic descriptive study with a cross-sectional design. The population in this study were mothers who had babies aged 0-6 months in the working area of the Saribudolok Health Center who were selected by simple random sampling by taking a sample of 30 respondents. The results showed a bivariate analysis of 30 respondents who had babies aged 0-6 months, which influenced mothers in providing complementary food for breastfeeding, namely education and family support, namely p-value 0.000x 0.5, while that did not affect age, occupation, socio-economic. So that everyone around the mother can provide support to the mother to improve the mother's perception regarding her milk production.